4w+8y+3x+9x-13y+4w=

Simple and best practice solution for 4w+8y+3x+9x-13y+4w= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4w+8y+3x+9x-13y+4w= equation:


Simplifying
4w + 8y + 3x + 9x + -13y + 4w = 0

Reorder the terms:
4w + 4w + 3x + 9x + 8y + -13y = 0

Combine like terms: 4w + 4w = 8w
8w + 3x + 9x + 8y + -13y = 0

Combine like terms: 3x + 9x = 12x
8w + 12x + 8y + -13y = 0

Combine like terms: 8y + -13y = -5y
8w + 12x + -5y = 0

Solving
8w + 12x + -5y = 0

Solving for variable 'w'.

Move all terms containing w to the left, all other terms to the right.

Add '-12x' to each side of the equation.
8w + 12x + -12x + -5y = 0 + -12x

Combine like terms: 12x + -12x = 0
8w + 0 + -5y = 0 + -12x
8w + -5y = 0 + -12x
Remove the zero:
8w + -5y = -12x

Add '5y' to each side of the equation.
8w + -5y + 5y = -12x + 5y

Combine like terms: -5y + 5y = 0
8w + 0 = -12x + 5y
8w = -12x + 5y

Divide each side by '8'.
w = -1.5x + 0.625y

Simplifying
w = -1.5x + 0.625y

See similar equations:

| 2x-2(x+11)=5x | | y=3x^2+16x-8 | | 4w+9x+11y+3w+3x-6y= | | 5p+7=4p+3 | | 5h-4=-16 | | x+3(x-1)=4 | | 9+2.71t=-4.8t-6 | | -x^2-2x-8=0 | | 24-x=18 | | -x^2-7x+22=0 | | M^2+7M=4 | | 2(x+3y-1)=y | | 5(x-y)+2y=-26 | | 7x-(3x-4)=8-6x-6+5x | | log(7)=2 | | 14.40+4.05p=4.50(3+p) | | y=13x+404+46 | | 3(3x-6)=1-2x | | x+(x-10)+2(x-10)+6=100 | | 3x^2-5xy+2y^2+3x=0 | | 2.8-5.6= | | 5y-30y+10=-52+2y-4y | | (x^2+x)-6= | | 5*24-3x=90 | | 3k-s=7k-21 | | 5(y+2)=4-7 | | =y-6y^3 | | -(x-1)-3(x+4)=x | | -(x-1)+3(x+4)=x | | 16x+12x=100 | | xy+2x-3y+2+12(x^2)y-3x(y^2)-12x+18y=16 | | 2(x-1)=-(x-3)+(4-x) |

Equations solver categories